Metrology 2018
DOI: 10.5772/intechopen.74220
|View full text |Cite
|
Sign up to set email alerts
|

Variational Calibration

Abstract: The approach to the improving the accuracy of the impedance parameter measurements is described. This approach is based on the well-known variations of the influence of the disturbing factors on the results of measurement. Using these variations, measurement circuit provides the additional number of measurements, equal to the number of the disturbing factors. System of equations describes these results of measurements. The solution of this system eliminates the influence of the appropriate uncertainty sources … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…Earlier studies have shown the possibility of significantly reducing these disadvantages due to the use of differential measurements using a measuring channel (MCh) with a balanced alternating current bridge [7][8][9][10][11][12]. The direction of their use with impedance sensors, in particular with conductometric ones, turned out to be very promising [6,9,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have shown the possibility of significantly reducing these disadvantages due to the use of differential measurements using a measuring channel (MCh) with a balanced alternating current bridge [7][8][9][10][11][12]. The direction of their use with impedance sensors, in particular with conductometric ones, turned out to be very promising [6,9,13,14].…”
Section: Introductionmentioning
confidence: 99%